Inventarisasi Tiga Jenis Famili Tumbuhan Berberda di Universitas Islam Negeri Sunan Gunung Djati Bandung - Nashwa Intana Putri; Nursyifa Tiara Dwiputri; Ateng Supriyatna (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Plants are eukaryotic organisms that are multicellular and autotrophic. Inventory is an action to collect data regarding biodiversity. The inventory process requires exploration and identification of a plant which includes the name of the type, number of types, size and benefits of the plant type. The plants around Uin Sunan Gunung Djati Bandung consist of several families, among which there are the Asparagaceae, Moraceae and Myrtaceae families. This research was conducted at the Sunan Gunung State Islamic University and aims to determine the types of plants of the Asparagaceae, Myrtaceae and Moraceae families located in that area. This research uses data collection techniques by direct observation in the area. Thus, this research is a descriptive qualitative research type. Based on the results of observations and exploration at Sunan Gunung Djati Islamic University, Bandung, 3 different families have been found, namely Asparagaceae with 4 different species, Myrtaceae with 2 different species and Moraceae with 3 different species.